Causes and Consequences of the Breakdown of the Middle East Peace Process (Journal of International Studies, 2020)
This paper reviews the main correlates for the failure of the Arab-Israeli peace process since its formal inception after the October 1973 War with special emphasis on the breakdown of the Palestinian-Israeli negotiations at the Camp David II Summit held in July 2000. The paper disproves the widely held notion that the Palestinian side was mainly behind such failure by comparing various narratives of the deliberations of the summit. It also looks at the main factors which have been influencing Arab-Israeli relations since September 11, 2001. These are the advent of a neo-conservative administration into power in the USA, the September 11 events in the USA, the invasion and occupation of Afghanistan and Iraq by the USA, and the change of Palestinian leadership. This paper shows the impact of these developments for the future of peace in the Middle East and attempts finally to outline the main lessons to be learnt from the failure of the Arab-Israeli peace process for the future of the Middle east.